Anetodermia primaria en paciente VIH positivo - Rodríguez Mendoza, Johanna; De Luca, David; Enz, Paula Andrea; Torre, Ana Clara; Volonteri , Victoria Inés; Galimberti, Ricardo (Revista del Hospital Italiano de Buenos Aires, 2012)
-